Catechol-O-methyltransferase gene variants may associate with negative symptom response and plasma concentrations of prolactin in schizophrenia after amisulpride treatment. (March 2016) - Chen, Chun-Yen; Yeh, Yi-Wei; Kuo, Shin-Chang; Ho, Pei-Shen; Liang, Chih-Sung; Yen, Che-Hung; Lu, Ru-Band; Huang, San-Yuan
Highlights: The COMT variants are associated with improvement of negative symptoms after amisulpride treatment. The COMT rs4680 variant is associated with the change of plasma prolactin levels after treatment. The variation in plasma prolactin levels might be a measurable biomarker of COMT variants and treatment outcomes. Abstract: Catechol- O -methyltransferase (COMT) enzyme is involved in the pathogenesis of psychotic symptoms and may be associated with a therapeutic response to antipsychotic drugs. The aim of this study was to examine the relationship between COMT variants, plasma prolactin level, and the therapeutic effectiveness of amisulpride treatment in patients with schizophrenia. A 12-week naturalistic study of amisulpride treatment was carried out in 185 Han Chinese patients with schizophrenia. The patients were screened for 14 single-nucleotide polymorphisms of the COMT gene. The Positive and Negative Syndrome Scale (PANSS) was used to assess the improvement of psychopathological symptoms from the baseline to the end point in each subject. For better presentation of time-course changes in response status, a mixed model for repeated-measures (MMRM) analysis of symptom improvement during the 12-week treatment period was conducted. The change in plasma prolactin level after amisulpride treatment was also examined ( n  = 51). No significant differences in the genotype frequencies of the COMT variants investigated were observed between responders and non-responders. Moreover, an MMRM analysis of psychopathological symptom improvement during the 12-week treatment course showed that it depended significantly on COMT variants (rs4680, rs4633, and rs6267), particularly regarding changes in negative symptoms. The increase in plasma prolactin levels observed was influenced by the COMT rs4680 variant and was positively correlated with a reduction in PANSS negative scores. Our results suggest that variation of the COMT gene is associated with treatment response regarding negative symptoms and prolactin changes after amisulpride treatment in patients with schizophrenia.